PENGARUH KNOWLEDGE SHARING DAN KOMPETENSI TERHADAP KOMITMEN PADA DINAS PUBMSDA KABUPATEN SIDOARJO - Yoga Dwi Anugrahadi; Gendut Sukarno; Ika Korika Swasti (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the effect of knowledge sharing and competence on a commitment to the PUBMSDA Office of Sidoarjo Regency. The population in this study were employees of the PUBMSDA Office of Sidoarjo Regency. The sampling method uses non-probability sampling, namely the purposive sampling technique. The sample taken amounted to 42 respondents. The data used are primary data, namely questionnaire data from respondents' answers, and secondary data, namely supporting data obtained from the PUBMSDA Office of Sidoarjo Regency. While the analysis used is Partial Least Square (PLS). Based on the research and discussion of research results, it has been found that knowledge sharing and competence positively affect a commitment to the PUBMSDA Office of Sidoarjo Regency.